Effecting Factors on Large Scale Production of Medicinally Active Compound in Garlic (Allium sativum) - Rajesh Kumar Singh; S. N. Hiremath (New Visions in Science and Technology Vol. 11, 2021)
The Objective of this study was “To identify the reason of medicinally active compound i.e. Alliin/Allicin content variations in various Alliums species which was cultivated in different region of Indian states. Garlic contains medicinally active compounds like Alliin/Allicin, Di-allyl Disulfide, 2-vinyl-4H-1, 3-dithiin, Ajoene. Alliin (Allicin) is cholesterol lowering and antihypertensive. Alliin is an amino acid, in presence of enzyme Alliinase, Alliin converted into Allicin and it has produce characteristic smell of garlic. Various samples of Garlic (varieties) collected from various locations (Climatic Condition) and Alliin is estimated from different parts of the plant.